Detecting deceptive behaviour after the fact. (22nd September 2015) - von Hippel, William; Baker, Ernest; Wilson, Robbie; Brin, Loic; Page, Lionel
Abstract : This study examined whether people can detect deception after the fact if they initially accept someone's behaviour at face value but then learn that they have been duped. Fifty‐four groups composed of four to six mutual friends engaged in a group discussion with a financial incentive for arriving at a correct decision. One member of each group was secretly assigned to sabotage the decision. Although none of the participants noticed the deception when it was committed, they showed substantial accuracy in identifying the saboteur once they were told that a deception had occurred. Nevertheless, interrogation did not increase the accuracy of their detection of deception. Participants showed a significant positive relationship between confidence and accuracy. Finally, participants also showed better‐than‐chance accuracy in their judgments of who believed them during the interrogation and who did not. These results suggest that the detection of deception might often be accomplished using information gained after the fact to reinterpret behaviours that were not initially suspected.